DAMPAK KONTEN PEMASARAN DI MEDIA SOSIAL TERHADAP CITRA DAN PENGARUHNYA PADA KEPUTUSAN MENDAFTAR DI PERGURUAN TINGGI - Khairani, Zulia; Kamilah, Faizah; Soviyanti, Efrita (Jurnal Ekonomi Bisnis Kompetif, 2023)
This research was conducted to determine and analyze the impact of marketing on social media on image and its influence on the decision to enroll in college. This research conducted a survey of students at private universities with b and excellent accreditation. The sample in this research was 100 people using a quota sampling method and this research used a quantitative approach with an inductive descriptive method, namely collecting, presenting, analyzing and testing hypotheses and compiling marketing content, institutional image and students' decisions to enroll in higher education according to their perceptions. first year student at a private university in Pekanbaru City. Quantitative analysis includes: validity and reliability tests and SEM analysis. Qualitative analysis is an interpretation of the data obtained in research as well as the results of data processing that has been carried out by providing information and explanations. The research results found that marketing content had a positive and significant influence on the decision to register, marketing content had a positive and significant influence on the institutional image, institutional image had a positive and significant influence on the decision to register, and institutional image was able to mediate the influence of marketing content on the decision to register at a private university in Pekanbaru city Keywords: Content Marketing, Institution Image, Student Decisions